Entre o passado e o presente: Adobe Lightroom e a memória afetiva na fotografia de Sóstenes Lopes - Araújo, Bruno Vinelli Nunes de Oliveira (2020)
Affective memories are archives of each person's emotional life history, which is why there are family albums (SILVA, 2008). The photos attest to the existence of what you want to show and are devices of memory. The advent of digital photography, in the 21st Century, expanded the editing resources of the images and enabled changes and manipulations that were not possible in analog photography. In Brazil, one of the programs used to manage and edit digital images is Adobe Lightroom, one of the digital tools that made the transition between analog and digital photography possible. The objective of this research was to analyze, by means of comparison, the influence of affective memory in the edition of an authorial photograph, named by the artist Sóstenes Lopes de 'Amor', using the Adobe Lightroom software. We applied the concepts of collective memory (HALBWACHS, 2015) and the act of photographing (SONTAG, 2004; SOULAGES, 2010; CARTIER-BRESSON, 2016) and used the qualitative approach and oral history as methodological procedures through the case study. We consider orality as a source for this research because it allows us to recover what we did not find in other documents, such as spontaneity, in addition to the image analysis procedures proposed by Fayga Ostrower (2018). The research presented the following results: in the work of the photographer / educator Sóstenes Lopes, the interaction between the human being and the machine was experienced in an intuitive way, using Adobe Lightroom, and manipulation was the moment to place the artist's signature in order to record the photographed instant, to show everyone that the subject photographed was (and still is) a moment related to various emotional reactions.